The transition of young people from education to employment in Brussels: challenges for governance - Abraham Franssen; Donat Carlier; Anissa Benchekroun (Brussels Studies)
The dualisation of the education system, early school leaving, the high unemployment rate of low-skilled young people and chronic insecurity underline the difficulties involved in the transition of low-skilled young people from education to employment. This synopsis is aimed at providing a better understanding of the transition of young people from education to employment, from unemployment to training, from training to employment and within the labour market itself. It is based on the observations of the “youth lab for the transition of young people from education to employment”, which for two years organised group analyses gathering institutional authorities, teachers, employers, professionals in the field and of course young unemployed people. After a quick review of the situation in Brussels and a specification of the category of “young people in transition”, the authors examine public action aimed at young people in transition. Secondly, a diagnosis of the implementation of this public action and its effects is established. With the stakeholders, it identifies some of the challenges of what is more a patchwork of cooperation between conflict-ridden relations than a coherent plan of action. Thirdly, from a prospective and propositional angle, the authors explore the conditions and ways of improving public action in terms of the transition of young people from education to employment.This synopsis is based on the observations of the “youth lab for the transition of young people from education to employment” (http://www.youthlab.eu). This research received the support of DG Employment and Social Affairs of the European Commission, and was conducted in partnership by Université Saint-Louis - Brussels, Actiris and CCFEE (Commission Consultative Formation Education Employment), as well as with three other public employment services: the Arbeitsmarktservice Österreich (AMS – Austria), the Bundesagentur für Arbeit (BA, Germany) and FOREM (Wallonia). For two years, it involved the various stakeholders in this transition in the Brussels Region in making a diagnosis and in building perspectives. The content of this synopsis commits solely its authors.